A Strategically Oriented System of Corporate Governance in Russian Companies with State Participation - I. Yu. Belyayeva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article examines the role of corporate governance in the implementation of long-term and innovative development programs in Russian companies with state participation. Practical recommendations on increasing the efficiency of companies with state participation have been developed. The analysis of the development and implementation of long-term development programs in Russian companies with state participation was carried out. A comprehensive analysis of innovative development programs of the largest Russian companies with state participation was carried out.